2010
DOI: 10.1071/rd09068
|View full text |Cite
|
Sign up to set email alerts
|

Detection of condensin I and II in maturing pig oocytes

Abstract: The multiprotein complexes known as condensins (I and II) are major players in chromosome dynamics in mitotic and meiotic cells. Here, we report for the first time the detection of different condensin subunits from both complexes in mammalian oocytes. Using immunoblotting analysis we examined expression levels of condensin subunits during meiotic maturation of porcine oocytes. The expression of the core subunit structural maintenance of chromosomes 2 (SMC2), identical in both condensin complexes, did not chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Although emerging studies in invertebrate model organisms have begun to uncover essential functions of condensins in meiotic chromosome structure and function, only fragmentary and limited information is available from studies in vertebrates such as Xenopus laevis (Watrin et al , 2003), pig (Liskova et al , 2010), and mouse (Viera et al , 2007). The present report is the first comprehensive study to investigate the expression, chromosomal localization, and potential functions of the two condensin complexes in mouse oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although emerging studies in invertebrate model organisms have begun to uncover essential functions of condensins in meiotic chromosome structure and function, only fragmentary and limited information is available from studies in vertebrates such as Xenopus laevis (Watrin et al , 2003), pig (Liskova et al , 2010), and mouse (Viera et al , 2007). The present report is the first comprehensive study to investigate the expression, chromosomal localization, and potential functions of the two condensin complexes in mouse oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Porcine oocytes were microinjected as was described previously [28]. Briefly, isolated oocytes were denuded and kept in supplemented M199 medium without hormones for 1 h at 38.5 °C.…”
Section: Methodsmentioning
confidence: 99%
“…An early study using mouse spermatocytes reported that a condensin I subunit (CAP-H) is concentrated on a fuzzy axial structure within chromatids in both meiosis I and meiosis II (Viera et al 2007). Whereas the existence of condensins I and II was initially reported in pig oocytes (Lisková et al 2010), a more recent study in mouse oocytes has described a comprehensive picture of the dynamics and function of condensins I and II (Lee et al 2011). At prophase of meiosis I (prophase I), condensin I is present in the cytoplasm, whereas condensin II is localized within the nucleus.…”
Section: Mammalsmentioning
confidence: 99%